PENGEMBANGAN INSTRUMEN ASESMEN BERBASIS WORDWALL UNTUK OPTIMALISASI HASIL BELAJAR EKONOMI - Hanna Hotmian Br Silalahi; Muhammad Bukhori Dalimunthe (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
This study aims to determine the validity, practicality, and effectiveness of Wordwall-based assessment instruments to optimize students' Economic learning outcomes. This research was conducted at SMA Negeri 1 Berastagi in the even semester of the 2024/2025 Academic Year. The research method used is the Research and Development (R&D) method with the ADDIE development model. The subjects in this study were students of class XI F-7 with the object of research in the form of Wordwall-based assessment instruments. Based on the results of the study, it was obtained that the assessment instrument developed was declared valid with a value of 0.8333 from material experts with very valid criteria and a value of 0.6875 from media experts with moderate criteria. It is stated as practical with the percentage of teacher response questionnaire of 87.50% and student response questionnaire of 84.70% with very practical criteria. It is stated as effective with an increase in completeness of 82.3% which based on the results of the N-Gain analysis obtained a value of 0.51154987 which is included in the moderate increase category. These results indicate that the Wordwall-based assessment instrument developed is stated as valid, practical, and effective for optimizing the learning outcomes of Economics students at SMA Negeri 1 Berastagi in the 2024/2025 academic year.